Plasma‐enhanced modification of multiwalled carbon nanotube with conducting polymers for dye sensitized solar cells. Issue 3 (11th March 2016) - Cogal, Sadik; Ela, Sule Erten; Cogal, Gamze Celik; Micusik, Matej; Omastova, Maria; Oksuz, Aysegul Uygun
Abstract : This study presents the modification of multi‐walled carbon nanotube (MWCNT) with poly(3‐hexylthiophene) (P3HT) and polypyrrole (PPy) through the fast, versatile, and environmentally friendly process of radiofrequency (RF)‐rotating plasma polymerization. Morphological characterization of composites was performed using scanning electron microscopy (SEM) and showed that the P3HT and PPy conducting polymers coated the MWCNT surface. The surface properties of the MWCNT composites were determined using Fourier transform infrared spectroscopy (FTIR), X‐ray photoelectron spectroscopy (XPS), and SEM analysis. MWCNT composites were used as cathodes in dye‐sensitized solar cells (DSSCs). The short circuit current densities of P3HT/MWCNT‐ and PPy/MWCNT‐based DSSCs were found to be 5.61 and 4.19 mA/cm 2, respectively. POLYM. COMPOS., 39:668–674, 2018. © 2016 Society of Plastics Engineers